2011
DOI: 10.1080/10496475.2011.560087
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Composition of the Dry Fruit ofTetrapleura tetrapteraand its Potential Impact on Human Health

Abstract: The chemical composition of Tetrapleura tetraptera, used traditionally as a spice and in African folk medicine, was determined. The proximate composition (%) based on dry weight was ash (3.17 to 3.48); crude protein (5.13 to 8.65); sugar (3.29 to 39.63); and starch (7.56 to 29.10). The mineral content (mg/kg) based on dry weight was Fe (29.69 to 65.06); Zn (5.35 to 25.16); Cu (4.00 to 12.54); Mg (392.35 to 2951.28); Mn (16.23 to 178.91);, Na (119.48 to 2364.93); Ca (1348.63 to 13839.86); K (8631.09 to 14881.0… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
33
3

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(41 citation statements)
references
References 20 publications
5
33
3
Order By: Relevance
“…The illnesses treated with it include hypertension, diuretic actions, management of convulsions, leprosy, rheumatic pain, diabetes mellitus, epilepsy, arthritis (1)(2)(3)9,13,24,25). The phytochemical properties of the plant have been investigated and found to possess mollucidal, antimicrobial, anticonvulsant, and toxic properties.…”
Section: Introductionmentioning
confidence: 98%
See 2 more Smart Citations
“…The illnesses treated with it include hypertension, diuretic actions, management of convulsions, leprosy, rheumatic pain, diabetes mellitus, epilepsy, arthritis (1)(2)(3)9,13,24,25). The phytochemical properties of the plant have been investigated and found to possess mollucidal, antimicrobial, anticonvulsant, and toxic properties.…”
Section: Introductionmentioning
confidence: 98%
“…The plant is a small tree found in tropical forest with features such as aerial fruits, which is made up of woody shell, fleshy pulp, and brownish-black seeds (9).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Food Resour. Sci., 4 (1): 17-22, 2015 are used as spices in the preparation of local dishes can be used to replace imported spices for seasoning meat products (Akin-Idowu et al, 2011;Adu-Adjei et al, 2014;Teye et al, 2014Teye et al, , 2015Amanfo et al, 2015). In West Africa, the plant Tetrapleura tetraptera (locally known as Prekese) is used as a spice, a medicine and as a dietery supplement rich in vitamins (Cangao, 2011;Abugri and Pritchett, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…In West Africa, the plant Tetrapleura tetraptera (locally known as Prekese) is used as a spice, a medicine and as a dietery supplement rich in vitamins (Cangao, 2011;Abugri and Pritchett, 2013). The fruit shell, fruit pulp and the seed of Tetrapleura tetraptera (Prekese) contain varying amounts of nutrients, such as protein, lipids and minerals, which are comparable with some popular spices, such as red pepper, onion, curry and ginger, so it use as spice to replace imported spices in meat products may not affect consumer acceptance (Akin-Idowu et al, 2011;Abugri and Pritchett, 2013). Lartey (2012) reported that the use of Prekese pod powder as a spice in sausage and burger showed a promising result in the sensory characteristics and nutritional qualities of the products.…”
Section: Introductionmentioning
confidence: 99%